WATER SUPPLY SYSTEM IN AGRICULTURE AND THEIR TECHNOLOGICAL EQUIPMENT - Vasylenkov, V. (Energy and Automation, 2016)
Presents the system of water supply in agriculture and studied their technological equipment. -language:EN-US’>Compensated m - phase (with m = 2k + 1≥3) and single-phase (m = 1) are similar in phase stator windings. Under the scheme rotary autotransformer (AT) from the capacitance at the output were made. The physical processes capacitance induction machines, energy efficiency and special terms of the principle of reversibility were detected.